Physical Exercise and Cardiac Repair: The Potential Role of Nitric Oxide in Boosting Stem Cell Regenerative Biology - Marino, Fabiola (Antioxidants (Basel), 2021)
Over the years strong evidence has been accumulated showing that aerobic physical exercise exerts beneficial effects on the prevention and reduction of cardiovascular risk. Exercise in healthy subjects fosters physiological remodeling of the adult heart. Concurrently, physical training can significantly slow-down or even reverse the maladaptive pathologic cardiac remodeling in cardiac diseases, improving heart function. The underlying cellular and molecular mechanisms of the beneficial effects of physical exercise on the heart are still a subject of intensive study. Aerobic activity increases cardiovascular nitric oxide (NO) released mainly through nitric oxidase synthase 3 activity, promoting endothelium-dependent vasodilation, reducing vascular resistance, and lowering blood pressure. On the reverse, an imbalance between increasing free radical production and decreased NO generation characterizes pathologic remodeling, which has been termed the “nitroso-redox imbalance”. Besides these classical evidence on the role of NO in cardiac physiology and pathology, accumulating data show that NO regulate different aspects of stem cell biology, including survival, proliferation, migration, differentiation, and secretion of pro-regenerative factors. Concurrently, it has been shown that physical exercise generates physiological remodeling while antagonizes pathologic remodeling also by fostering cardiac regeneration, including new cardiomyocyte formation. This review is therefore focused on the possible link between physical exercise, NO, and stem cell biology in the cardiac regenerative/reparative response to physiological or pathological load. Cellular and molecular mechanisms that generate an exercise-induced cardioprotective phenotype are discussed in regards with myocardial repair and regeneration. Aerobic training can benefit cells implicated in cardiovascular homeostasis and response to damage by NO-mediated pathways that protect stem cells in the hostile environment, enhance their activation and differentiation and, in turn, translate to more efficient myocardial tissue regeneration. Moreover, stem cell preconditioning by and/or local potentiation of NO signaling can be envisioned as promising approaches to improve the post-transplantation stem cell survival and the efficacy of cardiac stem cell therapy.